New species of Bakeriella (Hymenoptera, Bethylidae) from the New World and new data on geographic distribution - Kawada,Ricardo (2003)
Bakeriella lata sp. nov. (Brazil, Rondônia), Bakeriella aurata sp. nov. (Brazil, Amazonas) and Bakeriella sulcaticeps sp. nov. (Brazil, Amazonas) are described and illustrated. New geographic records and variation data for B. cristata Evans, 1964, B. floridana Evans, 1964, B. flavicornis Kieffer, 1910, B. incompleta Azevedo, 1994, B. mira Evans, 1997, B. montivaga (Kieffer, 1910), B. olmeca Evans, 1964 and B. subcarinata Evans, 1965 are provided. The male of B. incompleta is described for the first time.